UMPSA launches Study@UMPSA portal to strengthen digital marketing strategy - Naqiah, Puaad (UMPSA, 2025)
GAMBANG, 17 April 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) marked another important achievement in its digitalisation efforts by launching its official academic marketing portal, Study@UMPSA, which also features an artificial intelligence (AI)-based smart agent known as BURU.